Genetic Counseling for Diabetes Mellitus - Stein, Stephanie A. (2014)
Most diabetes is polygenic in etiology, with (type 1 diabetes, T1DM) or without (type 2 diabetes, T2DM) an autoimmune basis. Genetic counseling for diabetes generally focuses on providing empiric risk information based on family history and/or the effects of maternal hyperglycemia on pregnancy outcome. An estimated one to five percent of diabetes is monogenic in nature, e.g., maturity onset diabetes of the young (MODY), with molecular testing and etiology-based treatment available. However, recent studies show that most monogenic diabetes is misdiagnosed as T1DM or T2DM. While efforts are underway to increase the rate of diagnosis in the diabetes clinic, genetic counselors and clinical geneticists are in a prime position to identify monogenic cases through targeted questions during a family history combined with working in conjunction with diabetes professionals to diagnose and assure proper treatment and familial risk assessment for individuals with monogenic diabetes.